Self-sterilized composite membranes of cellulose acetate/polyethylene glycol for water desalination. (20th September 2016) - Ahmad, Adnan; Jamshed, Fahad; Riaz, Tabinda; Gul, Sabad-e-; Waheed, Sidra; Sabir, Aneela; AlAnezi, Adnan Alhathal; Adrees, Muhammad; Jamil, Tahir
Highlights: Two step phase inversion protocol was adopted to synthesize the membranes. Addition of Silver-DMF organosol to introduce the antibacterial properties. Hydrophilicity and Flux were enhanced in modified membranes. Reproducibility of data was done to confirm the results. Abstract: Cellulose acetate/Polyethylene glycol-600 composite membranes were fabricated by two step phase inversion procedure and modified by in-situ reduction of silver nitrate. FTIR spectra demonstrated the existence of functional groups for bonding of silver with oxygen at 370 cm −1, 535 cm −1 . The XRD diffractogram indicates characteristic peaks at 2θ values of 38.10°, 44.30°, 64.40°, and 77.30° which confirm the successful incorporation of silver within matrix of composite membranes. The morphology of composite membranes with appearances of spongy voids was exemplified from the scanning electron microscope. The atomic force microscopy was used to determine the increase in the surface roughness of the membranes. The increase in hydrophilicity, measured through contact angle, is rendered to the embedment of silver. The modification of membranes increased the flux from 0.80 to 0.95 L/hr.m 2 . The resulting membranes have outstanding ability to fight against gram negative Escherichia Coli and Bacillus Sabtilus . The novel cellulose acetate/polyethylene glycol membranes customized with silver have paved the path for evolution of axenic membranes.